Amebas testáceas (Arcellinida e Euglyphida) de diferentes biótipos de uma lagoa da planície de inundação do alto rio Paraná. - Alves, Geziele Mucio (2010)
In continental aquatic environments, testate amoebae have been studied at different biotopes, as sediment, aquatic macrophytes and plankton of rivers, reservoirs and lakes. However there are no studies that evaluate the community structure of these protists in these three biotopes within the same environment. Besides ecological studies, the biometric approach has been applied in the last two decades with testate amoebae. In this way, the present study quantified and tested the relationships of composition, abundance, morphological types and size structure of testate amoebae, between the communities present at different biotopes (plankton, aquatic macrophytes and sediment) from a marginal lake of the Upper Paraná River floodplain. During the study period the species identified in the plankton were not represented by the most abundant species in aquatic macrophytes and sediment. The most abundant species for the plankton was Difflugia gramen, while for macrophytes and sediment was Centropyxis aculeata. The predominant morphological type of the shell in plankton (spherical and hemispheric) was different from the other two biotopes (flattened and elongated). Regarding the size structure of the community, we recorded the predominance of smaller individuals in the plankton and larger ones, in sediment. During the high water period, we observed smaller sized individuals in all biotopes. Our results suggested that the planktonic biotope presents characteristic populations, able to produce gas vacuoles and shells with low density, higher abundance of shells formed by endogenous material, which ensure the success of these populations in this habitat. Moreover, the size differences are probably associated to metabolic activities, i.e., to energy requirements of these unicellular organisms at each biotope type.